María-Paz de Hoz, Juan Luis García Alonso and Luis Arturo Guichard Romero (eds), Greek paideia and local tradition in the Graeco-Roman east - Stavrou, Dorothea (Journal of Greek Archaeology, 2021)
Greek Paideia and Local Tradition in the Graeco-Roman East enriches our knowledge and understanding of the process of Hellenization in the Graeco-Roman East. In the foreword to the volume it is stated that its aim was to study this process especially in areas of Asia Minor and Egypt and to a lesser extent in Syria. The volume examines the various elements involved in the interaction between Greek and local cultures, to show how various aspects of Greek culture were adopted and transformed by indigenous populations who converted such features ‘into their own identity traits’. This collection of essays shows how the process of Hellenization that took place in the dynamic environment of the Graeco-Roman East, peopled by various ethnic entities, was modified and manipulated over time.